Penerapan Prinsip New Publik Service dalam Pelayanan STNK pada Kantor Sistem Administrasi Manunggal Satu Atap - Hendry Ch Soselisa; Diana Puturuhu (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2021)
The New Public Service (NPS) Paradigm is a concept that is made to "counter" the administrative paradigm that becomes themainstream, the New Public Management paradigm that has the principle "run government like a business"or "market as asolution to the ills in public sector ". This research is trying to find out the alternative strategy in improving public service quality with the implementation of New Public Service principle in the service of making Vehicle registration certificate The focuS of this literature review on humanistic-based public services (citizen serve not Customers), prioritizing public interest (seek the public interest) and accountability The implementation of the New public Service principles can improve the synergy of public services and the responsiveness of public service organizations to the needs of the community, the implementation of model citizen serves not Custumer, Seek the Public Interest and Public service accountability as part of the New public Service principle is an alternativeimprovement of public service quality.